A new PET/CT volumetric prognostic index for non-small cell lung cancer. Issue 1 (July 2015) - Zhang, Hao; Wroblewski, Kristen; Jiang, Yulei; Penney, Bill C.; Appelbaum, Daniel; Simon, Cassie A.; Salgia, Ravi; Pu, Yonglin
Highlights We propose a new PET/CT volumetric prognostic (PVP) index for NSCLC based on a Cox regression model. The PVP index is a combination of TNM stage and whole-body metabolic tumor volume. The PVP index was developed based on 328 consecutive NSCLC patients. It offers better prognostic accuracy than TNM stage or whole-body metabolic tumor volume alone.